Women, gender, and health: methodologies and training material: record of seminar-workshop - Badilla, Leda ed. (PAHO San JoseCR, 1992)
Presents a methodology which was proposed in the seminar-workshop to deal with the topics of women, gender and health, using a creative play approach. Deals with the exchange of training methodologies in health, the various countries have to implement, and the various material employed for training activities.